Narrativas de comunicación transmedia y los efectos de comportamiento y conducta en la generación Z del barrio Guayaquil de la parroquia Santa Rosa provincia Tungurahua, año 2022 - Guachi Canseco, Martha Estefannia (2022)
The present investigation determined the incidence of Transmedia Communication Narratives (platforms of different digital formats) and the effects of behavior and conduct in Generation Z of the Guayaquil neighborhood of the Santa Rosa parish, Tungurahua province. The objective of this topic is to verify the changes in behavior and conduct caused by technology. The research analyzes the events of the new Transmedia Communication Narrative and the effects they generate on the behavior and conduct of Generation Z of the Guayaquil neighborhood of the Santa Rosa parish, province of Tungurahua. The instruments for obtaining data were interviews, surveys, observation and direct dialogue aimed at the young people of Generation Z of the Guayaquil neighborhood of the Santa Rosa parish, Tungurahua province. With the information collected, the problems that impacted by technological evolution were determined.